1995
DOI: 10.1123/jab.11.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Techniques Used by Olympic Ski Jumpers in the Transition from Takeoff to Early Flight

Abstract: This study was concerned with identifying important flight characteristics of the ski jump at the end of the early flight phase and describing how these characteristics developed from the run-in through the takeoff and during the early flight phase. The K90 individual competition of the 1994 Olympic Winter Games was analyzed. The 2-D data (takeoff) were collected by a high-speed video camera, and the 3-D analysis (early flight) used an algorithm whereby two cameras followed the jumpers through the early flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 7 publications
4
52
0
Order By: Relevance
“…This group also exhibited higher explosiveness in the knee joint, supported by the higher knee extension angular velocity 5 m behind the edge of the hill, which is comparable to the fi ndings of Arndt et al (1995), who reported similar results as measured at the jumping hill edge. Janura et al (1999), in contrast, conducted a study with the Czech Republicʼs teams to compare competitors in diff erent age categories and found that the SJ group had a large ankle angle to the horizontal along with a small knee extension of the angular velocity at the jumping hill edge.…”
Section: Comparison Of the Nc Competitors And The Sj Groupsupporting
confidence: 85%
See 1 more Smart Citation
“…This group also exhibited higher explosiveness in the knee joint, supported by the higher knee extension angular velocity 5 m behind the edge of the hill, which is comparable to the fi ndings of Arndt et al (1995), who reported similar results as measured at the jumping hill edge. Janura et al (1999), in contrast, conducted a study with the Czech Republicʼs teams to compare competitors in diff erent age categories and found that the SJ group had a large ankle angle to the horizontal along with a small knee extension of the angular velocity at the jumping hill edge.…”
Section: Comparison Of the Nc Competitors And The Sj Groupsupporting
confidence: 85%
“…Thus, it is necessary to consider these diff erences in the comparison of the ski jump execution of the competitors at diff erent performance levels (Arndt, Brügemann, Virmavirta, & Komi, 1995;Schmölzer & Müller, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Lillehammer Winter Games indicated that less than 15% of the variance in total performance (distance jumped) could be explained by centre of mass (CoM) parameters at take-off (Arndt et al, 1995). Observation of ski jump competitors is used to determine parameters that influence the length of the jump.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, it can be suggested that the realization of take-off is probably very individual and that subjects perform the take-off using different combinations of take-off factors (Arndt Bruggemann, Virmavirta & Komi, 1995). Using statistical methods require a large number of take-offs by a large number of individuals under the same jumping conditions.…”
Section: Introductionmentioning
confidence: 99%